Hortas escolares nos anos iniciais do ensino fundamental: contribuições para o ensino de ciências - Enisweler, Kely Cristina (2017)
This research is based on the assumption of the development of different practices that provide better teaching and learning conditions for students and teachers in the initial years of Elementary School.Considering the timetable of contents directed to the Science Education in the initial training of teachers and that, in the great majority, the teachers of the initial years are undergraduated from the Pedagogy Courses.It becomes urgent the need to think about tools that collaborate for the continuous training of these professionals.Faced with this problem, the aim of this dissertation was to understand the meaning assigned to the space destined to school kitchen gardens -of the municipal schools of the urban perimeter in the city of Cascavel/PR, Brazil- and its importance for the development of teaching and learning Sciences, aiming to contribute to the implementation incentive of the pedagogic school garden,based on the assumption that they are a methodological tool for the development of a living laboratory constituted by kitchen gardens for different practices that provide better teaching and learning conditions for students and teachers in the early years of Elementary School.For its effectiveness, the research was unfolded in bibliographical, documentary and field. In the bibliographic part we considered articles, dissertations and doctoral theses on the theme.The document research was focused on the collection of documents made by the official organs linked to education and related to public policies regarding to the implementation of school kitchen gardens.The field research was carried out in two phases: (i) the first is consisted on the mapping of the school kitchen gardens in the municipal urban perimeter schools and their function; (ii) in the second phase, questionnaires were applied with teachers and students from schools that work with the pedagogic school kitchen garden to verify their importance in the teaching and learning process.The results of the research show that the practice of gardening in the school environment has not yet been part of pedagogical planning in most of the surveyed schools and that the main reason for this is the lack of time and a responsible person to work on this space.One of the possibilities pointed out in this work is the cultivation of kitchen garden in small spaces or as extracurricular activity.The data also highlight the need to think of this space as a pedagogical tool because, according to teachers and students who develop this activity, this has contributed significantly in the teaching and learning process.